Cervical Precancers and Cancers Attributed to HPV Types by Race and Ethnicity: Implications for Vaccination, Screening, and Management. (17th February 2022) - Mix, Jacqueline; Saraiya, Mona; Hallowell, Benjamin D; Befano, Brian; Cheung, Li C; Unger, Elizabeth R; Gargano, Julia W; Markowitz, Lauri E; Castle, Philip E; Raine-Bennett, Tina; Walker, Joan; Zuna, Rosemary; et al.
Abstract: Background: Racial and ethnic variations in attribution of cervical precancer and cancer to human papillomavirus (HPV) types may result in different HPV vaccine protection, screening test coverage, and clinical management. Methods: Pooling data from 7 US studies, we calculated the proportional attribution of precancers and cancers to HPV types using HPV DNA typing from diagnosis. All statistical tests were 2-sided. Results: For all racial and ethnic groups, most cases of cervical intraepithelial neoplasia grade 3 (CIN3) (84.2%-90.8% of 5526) and squamous cell carcinoma (SCC) (90.4%-93.8% of 1138) were attributed to types targeted by the 9-valent vaccine. A higher proportion of CIN3s were attributed to nonvaccine HPV types among non-Hispanic Black women (15.8%) compared with non-Hispanic Asian or Pacific Islander (9.7%; P  = .002), non-Hispanic White (9.2%; P  < .001), and Hispanic (11.3%; P  = .004) women. The proportion of SCCs attributed to 9-valent types was similar by race and ethnicity ( P  = .80). A higher proportion of CIN3s were attributed to nonvaccine HPV35 among non-Hispanic Black (9.0%) compared with non-Hispanic Asian or Pacific Islander (2.2%), non-Hispanic White (2.5%), and Hispanic (3.0%; all P  < .001) women. Compared with CIN3, the proportion of SCCs attributed to HPV35 among non-Hispanic Black women (3.2%) was lower and closer to other groups (0.3%-2.1%; P  = .70). Conclusion: The 9-valent HPV vaccine will prevent nearly all cervical precancers and invasive cancers among major racial and ethnic groups in the United States. Adding HPV35 to vaccines could prevent a small percentage of CIN3s and SCCs, with greater potential impact for CIN3s among Black women. HPV screening tests target high-risk HPV types, including HPV35. Future genotyping triage strategies could consider the importance of HPV35- and other HPV16-related types.